A 16 year study of injuries to professional kickboxers in the state of Victoria, Australia. Issue 5 (26th September 2003) - Zazryn, T R; Finch, C F; McCrory, P
Abstract : Objectives: To determine the rate and type of injuries occurring to registered professional kickboxers in Victoria, Australia over a 16 year period. Methods: Data describing all fight outcomes and injuries sustained during competition for the period August 1985 to August 2001 were obtained from the Victorian Professional Boxing and Combat Sports Board. Results: A total of 382 injuries were recorded from 3481 fight participations, at an injury rate of 109.7 injuries per 1000 fight participations. The most common body region injured was the head/neck/face (52.5%), followed by the lower extremities (39.8%). Specifically, injuries to the lower leg (23.3%), the face (19.4%), and intracranial injury (17.2%) were the most common. Over 64% of the injuries were superficial bruising or lacerations. Conclusion: The nature of kickboxing, whereby kicking the opponent is the prime movement and the head a prime target, is reflected in the distributions of body regions most commonly injured by participants. Further research into injury patterns in different styles of kickboxing and the mechanism of injury occurrence is required. Exposure adjusted prospective studies are needed to monitor injury rates over time.